ANALYSIS OF THE PREPARATION OF STANDARD OPERATING PROCEDURES (SOP) IN SUPPORTING COMMUNITY SATISFACTION AT THE BALUSU DISTRICT OFFICE, BARRU REGENCY - Masyitah Masyitah; Mukmin Muhammad; Armin Armin (Sean Institute, 2023)
This study aims to determine: To find out the preparation of SOPs that become public service standards at the Balusu District office and to determine the implementation of the preparation of Standard Operating Procedures (SOP) in supporting community satisfaction. The research method use disaqualitative method with data obtained through surveys, interviews, observation and documentation. The results of this study indicate that the preparation and application of SOPs in Balusu District according to the data collected, it is known that all of them have followed the applicable procedures in supporting the satisfaction of the people of Balusu District. The implementation of SOPsat the Balusu District Office has complied with public service standards, namely requirements, time for completion of applications, cost capacity, clarity of procedures, open ness and clarity of information, ease of submitting complaints and good understanding of office employees.